Work extraction from information ratchet in the classical and quantum regimes - He, Lianjie (Nanyang Technological University, 2024)
The focus of this thesis is to investigate the stochastic dynamics of two variants of an information ratchet inspired by a model interacting with an infinite tape of classical bits which play the role of an information reservoir. First, we explore the thermodynamics of a class of discrete-time autonomous information ratchet with a finite tape as a Maxwell demon. We demonstrate that it can operate both as an engine and eraser, and it eventually equilibrates due to the finite information capacity of the tape. Through successive tape scans, cumulative work is accrued, and we prove that this finite-tape information ratchet obeys the information processing second law (IPSL). We show that our information ratchet can harness correlation through accessing multiple ratchet states to accumulate more work by having a larger time constant to reach its steady state. We next utilise the marginal distribution as a mathematical tool to probe the effects of correlation which leads to the presence of equilibrium and nonequilibrium stationary states, and illuminate the differences in their steady-state behaviour. Second, we investigate into the possible maximum work extraction (ergotropy) of a quantum information ratchet that interacts with an infinite tape of qubits. Depending on the ratchet Hamiltonian and the qubit-ratchet interaction, we found an increase in its ergotropy even though the initial ratchet state has zero ergotropy, as the open system dynamics of the ratchet converges towards its stationary state.